British diplomacy and the Iranian revolution, 1978-1981 - Ali, Luman (2016)
Exploiting recently-released files from the United Kingdom’s National Archives at Kew, this thesis is a case study of the complexities of engaging in diplomacy with a revolutionary regime – a regime that had come to power in a state with which there had previously been friendly co-operation and profitable commercial relations. Specifically, it analyses the evolution of the British diplomatic experience and especially the role played by British diplomats in dealing with Iran between 1978, when widespread discontent against the Shah made it clear that his pro-Western regime might not survive, through the revolution of 1979, the dawn of the Islamic Republic and the American embassy hostage crisis, until the end of 1981, by which time it was clear that Anglo-Iranian relations were mired in difficulties, with Britain conducting business via an ‘interests section’ under a protecting power, Sweden. The main purpose of this thesis is to investigate how well British diplomats performed as they conducted relations during a major revolution, against a highly uncertain backdrop, with Iranian domestic affairs in constant flux. Comparisons are made to the British experience of previous revolutions, especially those in France, Russia and China.